The Relationship Between Knowledge and Attitudes of Young Women in Managing Vaginal Discharge at Senior High School - Martina Fenansia Diaz; Ririn Widyastuti (Poltekkes Kemenkes Kupang, 2023)
Vaginal discharge (leucorrhea) is a common reproductive health problem among adolescent girls. Adolescents need accurate information to remain alert and to practice healthy reproductive behavior, especially in interactions with the opposite sex. The occurrence of female reproductive tract diseases is generally caused by a lack of understanding among women about how to maintain hygiene and what actions should be taken to keep the reproductive organs healthy. Vaginal discharge can be physiological (normal) or pathological (abnormal), in which abnormal discharge is an early indication of infection or cancer. Vaginal discharge is one of the signs or symptoms of abnormalities in the female reproductive organs. Adolescence is a transitional period that often presents various growth and development issues, especially among girls whose cervix is biologically immature. This study aims to determine the relationship between knowledge and attitudes of adolescent girls in the management of vaginal discharge at SMA Negeri 2 Kupang. The research method used was cross-sectional. The study was conducted at SMA Negeri 2 Kupang, with a total population of 277 female students in grade XI. The sampling technique used was simple random sampling, resulting in a sample size of 55 respondents. Data were collected using a survey method with a questionnaire as the research instrument. The results showed that among respondents with poor knowledge, 15 students (78.9%) had a positive/supportive attitude and 4 students (21.1%) had a negative/non-supportive attitude toward the management of vaginal discharge. The Chi-square test indicated a significant level of 0.01, thus it can be concluded that there is a significant relationship between knowledge and attitudes of adolescent girls in the management of vaginal discharge.